1999
DOI: 10.1108/00251749910274234
|View full text |Cite
|
Sign up to set email alerts
|

Governance structures, size and corporate performance in UK firms

Abstract: Analyses the extent of Cadbury compliance and its impact on corporate performance in the UK. Comparing 1992 and 1995, we find that UK public companies have, in general, complied with the Cadbury Committee's Code of Best Practice and have adopted the recommended governance structures. However, compliance is more common among larger firms. Thus we find that duality is less common, firms tend to have more than three non-executive directors and that there has been an almost universal adoption of board subcommittee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
95
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 17 publications
(17 reference statements)
16
95
1
2
Order By: Relevance
“…Using 25 Canadian firms from 1976 to 2000, Bozec (2005) reports that CEO duality has no impact on market valuation. This is consistent with the results of previous studies (Baliga et al, 1996;Brickley et al, 1997;Rhoades et al, 2001;Vafeas and Theodorou, 1998;Laing and Weir, 1999;Weir and Laing, 2000;Sanda et al, 2010), which suggest that CEO duality has no impact on market valuation.…”
Section: The Theoretical and Empirical Literature On Dbls And Market supporting
confidence: 83%
See 1 more Smart Citation
“…Using 25 Canadian firms from 1976 to 2000, Bozec (2005) reports that CEO duality has no impact on market valuation. This is consistent with the results of previous studies (Baliga et al, 1996;Brickley et al, 1997;Rhoades et al, 2001;Vafeas and Theodorou, 1998;Laing and Weir, 1999;Weir and Laing, 2000;Sanda et al, 2010), which suggest that CEO duality has no impact on market valuation.…”
Section: The Theoretical and Empirical Literature On Dbls And Market supporting
confidence: 83%
“…The chairman of the board is responsible for managing the board. These may typically include nominating new board members, reviewing the performance of senior management, setting agenda for board meetings, and settling conflicts which may arise within the board (Laing and Weir, 1999). In contrast, the CEO is responsible for the day-to-day management of the company, including implementing board decisions.…”
Section: Cg Ntim Does the South African Stock Market…mentioning
confidence: 99%
“…However, the relationship between audit committee (AUCOM) and operating performance (ROA) is not significant in individual years except for model 1 of the pooled data when audit committee exerts significant positive impact on operating performance. This result supports H3 and agrees to the findings in studies of Laing and Weir (1999), Bouaziz (2012) and Kallamu and Saat (2015) which indicated that audit committee is significantly positively associated with financial performance. In addition, the board diversity (BDV) is found to be significant to operating performance (ROA) in model 2 in 2010 as well as for the pooled data.…”
Section: Multivariate Analysissupporting
confidence: 82%
“…Using UK firms, Laing and Weir (1999) found out that the presence of audit committee has positive impact on corporate performance. In the same vein, Bouaziz (2012) who used Tunisian firms reported that audit committee has positive impact on financial performance.…”
Section: Audit Committeementioning
confidence: 99%
See 1 more Smart Citation